Brain serotonin signaling does not determine sexual preference in male mice. - Mariana Angoa-Pérez; Nieves Herrera-Mundo; Michael J Kane; Catherine E Sykes; John H Anneken; Dina M Francescutti; Donald M Kuhn (PLoS ONE, 2015)
It was reported recently that male mice lacking brain serotonin (5-HT) lose their preference for females (Liu et al., 2011, Nature, 472, 95-100), suggesting a role for 5-HT signaling in sexual preference. Regulation of sex preference by 5-HT lies outside of the well established roles in this behavior established for the vomeronasal organ (VNO) and the main olfactory epithelium (MOE). Presently, mice with a null mutation in the gene for tryptophan hydroxylase 2 (TPH2), which are depleted of brain 5-HT, were tested for sexual preference. When presented with inanimate (urine scents from male or estrous female) or animate (male or female mouse in estrus) sexual stimuli, TPH2-/- males show a clear preference for female over male stimuli. When a TPH2-/- male is offered the simultaneous choice between an estrous female and a male mouse, no sexual preference is expressed. However, when confounding behaviors that are seen among 3 mice in the same cage are controlled, TPH2-/- mice, like their TPH2+/+ counterparts, express a clear preference for female mice. Female TPH2-/- mice are preferred by males over TPH2+/+ females but this does not lead to increased pregnancy success. In fact, if one or both partners in a mating pair are TPH2-/- in genotype, pregnancy success rates are significantly decreased. Finally, expression of the VNO-specific cation channel TRPC2 and of CNGA2 in the MOE of TPH2-/- mice is normal, consistent with behavioral findings that sexual preference of TPH2-/- males for females is intact. In conclusion, 5-HT signaling in brain does not determine sexual preference in male mice. The use of pharmacological agents that are non-selective for the 5-HT neuronal system and that have serious adverse effects may have contributed historically to the stance that 5-HT regulates sexual behavior, including sex partner preference.